2014
DOI: 10.1111/cea.12375
|View full text |Cite
|
Sign up to set email alerts
|

Elevated receptor for activated C kinase 1 expression is involved in intracellular Ca2+ influx and potentially associated with compromised regulatory T cell function in patients with asthma

Abstract: We confirmed that T(regs) in patients with asthma are functionally impaired and that the abnormal regulatory functions of these cells can be analysed by [Ca(2+)](i) following TCR engagement. Furthermore, the impaired functioning of T(regs) evident in patients with asthma may be due to a high level of RACK1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Moreover, in the lungs of OVA‐challenged mice, we observed higher protein expressions of TGF‐β1 and RACK1, the downstream target gene of TGF‐β1, in comparison with control mice. Interestingly, RACK1 has been identified as a multifunctional anchoring or adaptor protein in regulating cell growth, differentiation and migration and is potentially associated with asthma . In this study, consistent with previous reports, we found RACK1 was located at the airway epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, in the lungs of OVA‐challenged mice, we observed higher protein expressions of TGF‐β1 and RACK1, the downstream target gene of TGF‐β1, in comparison with control mice. Interestingly, RACK1 has been identified as a multifunctional anchoring or adaptor protein in regulating cell growth, differentiation and migration and is potentially associated with asthma . In this study, consistent with previous reports, we found RACK1 was located at the airway epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…Receptor for activated protein kinase C 1 (RACK1), an integral component of ribosomes, is located at the basal airway epithelial cells that functions as the downstream target gene of TGF‐β1 and plays an important role in multiple biological responses, including cell growth, differentiation, as well as migration . Our previous study demonstrated that OVA challenge significantly induced EMT process in airway epithelium via up‐regulation of TGF‐β1/RACK1, which is consistent with the report that knockdown RACK1 significantly inhibits the activation of TGF‐β/Smad signalling pathway in renal fibrosis . Moreover, it has been confirmed that RACK1 is required for regulating apoptosis although the role of RACK1 in regulating apoptosis remains controversial .…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is also possible that certain binding partner(s) of RACK1 other than the autophagy-initiation complex compensates the defects originated from impaired autophagy in Treg cells. In line with this notion, it has been suggested that RACK1 is involved in intracellular Ca 2+ influx in Treg cells (37). Besides, RACK1 may anchor Lck, PKC, and GRID (Grb2-related protein with insert domain) to function in T cell signaling pathways (38, 39).…”
Section: Discussionmentioning
confidence: 77%
“…Recently, PFOS was shown to suppress IL-2 production in both human T cell lines and primary T-cells [55], indicating that the disruption of TCR signaling by PFOS exposure might cause the arrest of T-cell proliferation and altered immune responses. Interestingly, Negoro and coworkers [56] showed that the incidence of asthma was caused by an increase in [Ca 2þ ] i of regulatory T-cells following TCR activation, with partial loss of regulatory functions, indicating that PFOS-induced calcium influx and TCR activation might be responsible for juvenile asthma, as reported by Dong et al [14].…”
Section: Discussionmentioning
confidence: 78%